Tackling causes and consequences of health inequalities : a practical guide - Matheson, James; Patterson, John, Dr.; Neilson, Laura (Boca Raton : CRC Press, 2020)
"Addressing health inequalities is a key focus for health and social care organizations, yet this is the first book to explore how best frontline health workers in areas of deprivation can address these problems. This book offers a concise but comprehensive overview of the key issues in health inequalities and how practically to address them"--
33 Working with People in Contact with the Criminal Justice System and in Secure Environments -- 34 Mental Health and Primary Care Management of Complex Psychiatric Conditions -- Part 4 Successful Models of Learning and Practice -- 35 A GP Curriculum for Health Equity -- 36 Examples of Innovative Service Models Across the UK -- 37 Widening Participation in Medical Education -- Index
OCLC-licensed vendor bibliographic record.
Keywords: Public health -- Social aspects; Social medicine; Health services accessibility; Equality -- Health aspects; MEDICAL / General; MEDICAL / Family & General Practice; MEDICAL / Public Health